Shaping the Digital Fashion Industry with Generation Z’s Buying Behavior - Prayataneswara Dwiputri Susanto; Christian Haposan Pangaribuan; Santo Tjhin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
Abstract: Marketing forms have evolved over time, and as the world transitions into a new generation of audiences and consumption behaviors, marketing has gone from the traditional to the more essential digital form, with the use of social media technology such as Instagram and Facebook. The main objective of this study is to empirically examine how hedonic motives, emotional response, and involvement in fashion can impact impulsive buying in the fashion industry within Generation Z. In this context, data were collected from 100 respondents in the age range of 16 to 23 years in the greater areas of Jakarta and Surabaya through an online survey. The data were then tested and finally analyzed. The most influential determinants affecting impulse buying are involvement in fashion, followed by hedonic motives, and emotional response. Even though the scarcity factor fills the gap created by prior studies’ inconsistencies, it fails to moderate the link between emotional response and impulse buying. Keywords: Impulse buying, Hedonic behavior, Emotional response, Involvement in fashion, Scarcity